EVOLUTION OF THE FUNCTIONAL AND TERRITORIAL STRUCTURE OF PUBLIC RAIL TRANSPORT IN KYIV - KOLOTUKHA, Oleksandr; KOLOTUKHA, Ihor (Ekonomichna ta Sotsialna Geografiya, 2023)
Urban transport systems require increased attention as connecting elements that affect the efficiency of the functioning of cities as a whole and individual districts. Public passenger transport of a large city, which is the capital of the state – Kyiv, is one of the branches of its life support, on the functioning of which both the development of the economic complex and the lifestyle of the population depend. The problem of the rational functioning of public transport and its territorial organization become one of the main ones for our capital during the martial law and will become critical after the Victory. The development of rail transport is a priority for any European city: it has the highest carrying capacity, it is environmentally friendly and comfortable for passengers, and most importantly, it does not depend on the amount of traffic jams. In Kyiv, there are four types of rail public transport - metro, tram (including high-speed tram), city electric train and funicular.The analysis of the evolution of the territorial structure of the urban rail public transport system, carried out using the methods of graph theory and historical-geographic sections, shows that this structure developed dynamically along with the development of Kyiv. It is substantiated that the priority directions of the development of Kyiv's transport system are aimed at the formation of a highly efficient transport complex capable of meeting the needs of the population in relevant services and minimizing the negative impact on the environment. To achieve this goal, the main directions of the development of Kyiv's rail public transport system have been determined: the priority of public passenger transport in the performance of city transportation; development of high-speed off-street types of public rail transport (metropolitan, high-speed tram, city railway); provision of fast, comfortable and safe transport connections between all functional zones of the capital on the basis of increasing the density of the street network, creating a system of complex transfer nodes at the stations of the metro and city railway lines.

Міські транспортні системи потребують підвищеної уваги як сполучні елементи, що впливають на ефективність функціонування міст в цілому та окремих районів. Громадський пасажирський транспорт великого міста, яким є столиця держави – м. Київ, є однією з галузей його життєзабезпечення, від функціонування якої залежить як розвиток господарського комплексу, так і спосіб життя населення. Проблема раціонального функціонування громадського транспорту, його територіальна організація постають одними з основних для нашої столиці під час воєнного стану та критично постане після Перемоги. Розвиток рейкового транспорту – пріоритет будь-якого європейського міста, адже у нього найвища провізна здатність, він екологічний і комфортний для пасажирів, і головне – він не залежить від кількості заторів на дорогах. В Києві представлені чотири види рейкового громадського транспорту – метрополітен, трамвай (в тому числі швидкісний трамвай), міська електричка та фунікулер. Аналіз еволюції територіальної структури системи міського рейкового громадського транспорту, здійснений за допомогою методів теорії графів та історико-географічних зрізів, свідчить про те, що ця структура динамічно розвивалася разом із розвитком Києва. Обґрунтовано, що пріоритетні напрями розвитку транспортної системи Києва спрямовані на формування високоефективного транспортного комплексу, здатного забезпечити потреби населення у відповідних послугах та мінімізувати негативний вплив на навколишнє середовище. Для досягнення цієї мети основними напрямами розвитку системи рейкового громадського транспорту Києва визначено: пріоритет громадського пасажирського транспорту у виконанні міських перевезень; розвиток швидкісних позавуличних видів громадського рейкового транспорту (метрополітену, швидкісного трамвая, міської залізниці); забезпечення швидкого, комфортного і безпечного транспортного сполучення між усіма функціональними зонами столиці на основі збільшення щільності вуличної мережі, створення системи комплексних пересадочних вузлів на станціях ліній метрополітену та міської залізниці.
ЕВОЛЮЦІЯ ФУНКЦІОНАЛЬНО-ТЕРИТОРІАЛЬНОЇ СТРУКТУРИ РЕЙКОВОГО ГРОМАДСЬКОГО ТРАНСПОРТУ КИЄВА
Keywords: city public transport; rail transport; functional-territorial structure; methods of graph theory; method of historical-geographic sections; Kyiv; громадський транспорт міста; рейковий транспорт; функціонально-територіальна структура; методи теорії графів; метод історико-географічних зрізів; Київ